In-vivo thermodynamic exploration of gas-based intraperitoneal hyperthermia - Diakun, Agata; Khosrawipour, Tanja; Mikolajczyk-Martinez, Agata; Kuropka, Piotr; Nicpoń, Jakub; Kiełbowicz, Zdzisław; Prządka, Przemysław; Liszka, Bartłomiej; Li, Shiri; Lau, Hien; Kielan, Wojciech; Khosrawipour, Veria (Frontiers in Oncology, 2022)
Background While hyperthermic intraperitoneal (i.p) applications are highly efficient in treating peritoneal metastases (PM), they are currently limited to temperatures of 41 – 43° Celsius (C). First data on gas-based i.p. hyperthermia is promising, as this novel method allows a significant temperature rise in superficial peritoneal layers without increasing core temperatures. Until now, key mechanisms of this novel tool, e.g. thermodynamic energy transfer, have not been investigated. This study aims to explore the volume of thermodynamic energy transfer during gas-based i.p. hyperthermia at 48-50°C and its peritoneal effects. Methods For this study, three swine were subjected to gas-based i.p. hyperthermia at varying temperatures (48°, 49° and 50°C) in a diagnostic laparoscopy setting with a high-flow air stream. Temperatures of the i.p. cavity, in- and outflow airstream at the trocar were measured and the thermodynamic energy transfer was calculated. Tissue samples were collected on postoperative day 7 for histopathologic analyses. Results According to our data, temperatures within the intraabdominal cavity and at the outflow site remain relatively stable at < 40°C. An increase in thermodynamic energy transfer is observed with increasing applied temperatures. Gas-based i.p. hyperthermia induced capillary coagulation and white blood cell infiltration within peritoneal layers. Conclusions Gas-based i.p. hyperthermia is an innovative approach which enables the i.p. delivery of specific amounts of thermodynamic energy. Following this procedure, our data indicate remarkable histologic changes on the superficial peritoneal layer most likely attributable to the applied thermodynamic energy. Further studies are required to investigate how these findings can be applied in PM management.